بلوچستان میں نظام قضاء وتحکیم: Islamic Law in Baluchistan Judiciary System - Muhammad, Niaz; Baz Muhammad, Dr. Sahibzada (Journal of Quranic and Social Studies, 2022)
The Department of Islamic law was established In Baluchistan absent during the reign of the rightly guided caliphs. After the disintegration of abased, it remained under the control of the Islamic caliphate. Baluchistan become an independent of state but Mehmood Ghaznavi included it in his empire during the reign. The Baloch government was established in Kalat in 1530 A.D. As Muslim they turned to shariah for solution their problems. First, in 1866 Khan Ahmed Yar Khan officially introduced the judiciary in Baluchistan which proved to be beacon for all latter Baloch rulers. In the meantime, due to the intervention of the British, although this chain was slightly weakened, but until 1933. Khan Ahmed Yar Khan ii tried to implement a complete sharia system In Baluchistan. The book “Moheen ul Qazat wal Muftiyyan” compiled by Allama Shams ul Haq Afghani is a happy line of this series.